Existence and Uniqueness of Fixed Points for Mixed Monotone Operators with Application (Communications in Mathematical Research, 2019)
In this paper, a class of mixed monotone operators is studied. Somenew fixed point theorems are presented by means of partial order theory, and theuniqueness and existence of fixed points are obtained without assuming the operatorto be compact or continuous. Our conclusions extend the relevant results. Moreover,as an application of our result, the existence and uniqueness of positive solution fora class of fractional differential equation boundary value problem are proved.